Cerium oxide nanoparticles improve cotton salt tolerance by enabling better ability to maintain cytosolic K+/Na+ ratio - Liu, Jiahao; Li, Guangjing; Chen, Linlin; Gu, Jiangjiang; Wu, Honghong; Li, Zhaohu (Journal of nanobiotechnology, 2021)
Salinity is a worldwide factor limiting the agricultural production. Cotton is an important cash crop; however, its yield and product quality are negatively affected by soil salinity. Use of nanomaterials such as cerium oxide nanoparticles (nanoceria) to improve plant tolerance to stress conditions, e.g. salinity, is an emerged approach in agricultural production. Nevertheless, to date, our knowledge about the role of nanoceria in cotton salt response and the behind mechanisms is still rare. We found that PNC (poly acrylic acid coated nanoceria) helped to improve cotton tolerance to salinity, showing better phenotypic performance, higher chlorophyll content (up to 68% increase) and biomass (up to 38% increase), and better photosynthetic performance such as carbon assimilation rate (up to 144% increase) in PNC treated cotton plants than the NNP (non-nanoparticle control) group. Under salinity stress, in consistent to the results of the enhanced activities of antioxidant enzymes, PNC treated cotton plants showed significant lower MDA (malondialdehyde, up to 44% decrease) content and reactive oxygen species (ROS) level such as hydrogen peroxide (H.sub.2O.sub.2, up to 79% decrease) than the NNP control group, both in the first and second true leaves. Further experiments showed that under salinity stress, PNC treated cotton plants had significant higher cytosolic K.sup.+ (up to 84% increase) and lower cytosolic Na.sup.+ (up to 77% decrease) fluorescent intensity in both the first and second true leaves than the NNP control group. This is further confirmed by the leaf ion content analysis, showed that PNC treated cotton plants maintained significant higher leaf K.sup.+ (up to 84% increase) and lower leaf Na.sup.+ content (up to 63% decrease), and thus the higher K.sup.+/Na.sup.+ ratio than the NNP control plants under salinity stress. Whereas no significant increase of mesophyll cell vacuolar Na.sup.+ intensity was observed in PNC treated plants than the NNP control under salinity stress, suggesting that the enhanced leaf K.sup.+ retention and leaf Na.sup.+ exclusion, but not leaf vacuolar Na.sup.+ sequestration are the main mechanisms behind PNC improved cotton salt tolerance. qPCR results showed that under salinity stress, the modulation of HKT1 but not SOS1 refers more to the PNC improved cotton leaf Na.sup.+ exclusion than the NNP control. PNC enhanced leaf K.sup.+ retention and Na.sup.+ exclusion, but not vacuolar Na.sup.+ sequestration to enable better maintained cytosolic K.sup.+/Na.sup.+ homeostasis and thus to improve cotton salt tolerance. Our results add more knowledge for better understanding the complexity of plant-nanoceria interaction in terms of nano-enabled plant stress tolerance.